Apert Syndrome: Dental management considerations and objectives - Line Droubi; Mohannad Laflouf; Yasser Alsayed Tolibah; John C. Comisi (Elsevier, 2022)
Background: Apert syndrome (AS) is a rare congenital disorder that correlates with many craniofacial features, like craniosynostosis, midfacial malformation, and symmetrical syndactyly of the hands and feet. Aim: This paper describes the facial and oral manifestations in a 20-year-old female previously diagnosed with AS, discusses the complex dental treatment plan and treatments, including the use of a customized toothbrush handle to enhance the patient's brushing ability. Results: A satisfactory outcome was provided, and the patients quality of life improved significantly due to this comprehensive multi-disciplinary care process. Conclusions: Comprehensive examination, extensive medical history reviewed, parental and patient consent are needed to establish a comprehensive treatment plan regarding the special needs of these patients.